Meningkatkan Kompetensi Guru dalam Penggunaan Media dan Aplikasi Pembelajaran Daring di UPT SD Negeri Sindangmandi - Ilham Imaduduin; Darmawan Darmawan (Jurnal Pengabdian Masyarakat PGSD, 2022)
Google Meet and Power Point are applications and media that are often used to help with online learning or distance learning. The process of introducing the Google Meet application and Power Point media as a form of effective learning activity platforms during the Covid-19 period. The program purpose is to make students of State of Elementary School of Sindangmandi, Baros District, Serang Regency not bored in participating in online learning. This program is the goal of the UPI 2021 Thematic Field Study program as a community service in the field of Education. The method used is to provide assistance to the teachers of State of Elementary School Sindangmandi about the use of the Google Meet application and Power Point media. It is intended so that the teachers can use these applications and media as online learning media in online learning. The authors hope the workshop and assistance will bring effective learning because of the interaction between teachers and students. The assistance was carried out during July 2021. The assistance was carried out offline at school and the discussion stage was online through WhatsApp groups. The target of this program is the teacher council of State of Elementary School of Sindangmandi who were still not familiar with the use of the application. With this activity, the teacher of State of Elementary School Sindangmandi can succeed in making Power Point media and use them in virtual meeting through Google Meet.